TerraSAR-X SAR data for classification of ice-free areas and glacier facies on Fildes Peninsula, King George Island, Antarctica - ANDRÉ M. DE ANDRADE; ROBERTO F.M. MICHEL; KÁTIA K. DA ROSA; ULISSES F. BREMER; CARLOS ERNESTO G.R. SCHAEFER; JEFFERSON C. SIMÕES (Anais da Academia Brasileira de Ciências)
Abstract The region of the Maritime Antarctic suffers significantly from climate change, resulting in regional warming and consequently affecting coverage. This study characterized three surface zones of Collins Glacier and three other zones in ice-free areas on the Fildes Peninsula, which has an area of 29.6 km². We used TerraSAR-X satellite images from 2014 to 2016 and analyzed the influence of meteorological and environmental conditions on these surface zones. We used five images from the TerraSAR-X satellite, three of these data were obtained during the same period of fieldwork. The classification considered three classes on the glacier (higher moisture, transition in moisture, and lower moisture) and three on the ice-free areas (wet snow, transition wet snow-bare ice, and bare ice), using Maximum Likelihood and ISODATA methods. In low-altitude glaciers with maritime influence, such as Collins, monitoring variations in surface zones is essential because the continuous increase in exposed ice may indicate potential retreat. The TerraSAR-X images enabled the classification of land features, highlighting the potential for continuous monitoring in the Maritime Antarctic, regardless of weather conditions and solar illumination.